Imaging the transient heat generation of individual nanostructures with a mechanoresponsive polymer - Xueqin Chen (Nature Portfolio, 2017)
Remote thermometers with a high spatiotemporal resolution are very desirable for applications in the life sciences, including photothermal therapy. Here, Chen et al. develop polymer coated gold nanorods with a temperature sensitivity of 80 mK and a 4 ms response time for thermometry in the life sciences.